ISOTOPIC-GEOCHEMICAL CHARACTERISTICS AND DEEP-SEATED SOURCES OF THE ALKALI ROCKS OF THE PEKTUSAN VOLCANO - Sakhno V.G. (My University, 2007)
Late Cenozoic volcanic rocks are widespread in the Russian Far East. They are mainly represented by eruptions of basaltic lavas, which compose the Sovgavan, Nelminskii, Shufanskii, and Shkotovskii plateaus, among others. Alkali basalts with xenoliths of spinel lherzolites compose monogenetic volcanoes and their vents along the deep-seated Tan Lu fault system in Northeast China and in the Ussuri–Amur rift system of the Primor’e and Amur regions, as well as along the faults of the Tokin Stanovik. Some volcanoes (Bolonski, Udalyanchi, Keluo, and others) consist of potassic alkali basaltoids (leucitic basanites, leucitites, trachybasalts, and other rocks).